Large deviations for nematic liquid crystals driven by pure jump noise. (6th June 2018) - Zhang, Rangrang; Zhou, Guoli
Abstract : In this paper, we establish a large deviation principle for a stochastic evolution equation, which describes the system governing the nematic liquid crystals driven by pure jump noise. The proof is based on the weak convergence approach.